Ciberbullying - New electronic technology for school bullying in two Lima-Peru districts - Oliveros, Miguel (2012)
Problem: The mass media often reports cases of school violence expressed as bullying and less frequently as cyberbullying. Objectives: To determine cyberbullying characteristics in public and private school children from two Lima districts as well as factors associated with electronic aggression. Design: Cross-sectional survey. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru; and Universidade Federal da Bahia, Brasil. Participants: Elementary and high school students. Methods: Cross-sectional survey in 2596 5th grade of elementary school to 5th grade of high school students from two private and six public schools. The Rosario Ortega measuring instrument was modified and validated with Cronbach test (0.872). The study was approved by the Ethics Committee and school principals. It also received the assent of participants and was respectful of ethical considerations in human research. Main outcome measures: Cyberbullying characteristics. Results: Cyberbullying was reported in 27.7% of the students surveyed, 21% in public schools and 41.2% in private schools. Aggressors and victims with cell phone and internet were more common in private schools. To have cell phones, computers in their rooms, internet access out of home and paid work were risk factors for cyberbullying. Cell phone and internet attackers were predominantly male and high schoolers. Having a cell phone was associated with aggression with this device, and outdoor internet access facilitated internet aggression. Conclusion: Presence of cyberbullying was very high, and should be considered a public health problem. It was more common in private schools than in public schools, and existed beginning at primary level.